Comparison Study on the Performances of Finite Volume Method and Finite Difference Method - Renwei Liu; Dongjie Wang; Xinyu Zhang; Wang Li; Bo Yu (Journal of Applied Mathematics, 2013)
Vorticity-stream function method and MAC algorithm are adopted to systemically compare the finite volume method (FVM) and finite difference method (FDM) in this paper. Two typical problems—lid-driven flow and natural convection flow in a square cavity—are taken as examples to compare and analyze the calculation performances of FVM and FDM with variant mesh densities, discrete forms, and treatments of boundary condition. It is indicated that FVM is superior to FDM from the perspective of accuracy, stability of convection term, robustness, and calculation efficiency. Particularly ,when the mesh is coarse and taken as 20×20, the results of FDM suffer severe oscillation and even lose physical meaning.